2018
DOI: 10.33899/mjn.2018.160076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses' Practices Concerning Blood Pressure Measurements

Abstract: Background and Aim-Blood Pressure Measurement (BPM) is considered a generic skill required in nursing, by a range of health professionals, for effective health assessment. The study aimed to assess nurses' techniques regarding correct way of measurement of blood pressure. Methods and Materials-A cross-sectional study was conducted on (241) nurses obtained accidently from different wards or units in three teaching hospitals in Mosul City/Iraq during a period "20 th of novmber 2017 to 20 th of January / 2018". T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The result of the present study in table (3) showed the effected evaluating of nursing note documentation in chart form by (15) items under 3 level scale its (never, sometime and always). table shows that the majority of the study sample never be document the name of ward, patient age, patient gender, the time of writing the nursing notes, nursing notes every four hours, changes in the patient's condition, such as refuse from taking treatment, the nurse name and signature after documentation all nursing note.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The result of the present study in table (3) showed the effected evaluating of nursing note documentation in chart form by (15) items under 3 level scale its (never, sometime and always). table shows that the majority of the study sample never be document the name of ward, patient age, patient gender, the time of writing the nursing notes, nursing notes every four hours, changes in the patient's condition, such as refuse from taking treatment, the nurse name and signature after documentation all nursing note.…”
Section: Discussionmentioning
confidence: 59%
“…Despite the wide recognition of the importance of quality nursing documentation and efforts made to enhance it, there are inconsistencies in the definition of good nursing documentation because of variations in nursing documentation practice based on different local requirements, documentation systems and terminologies across countries and settings. In research settings, the quality of nursing documentation has been assessed by various auditing instruments with different criteria reflecting how quality was perceived by the researchers (3).…”
Section: Introdctionmentioning
confidence: 99%
“…Most (52%) were in their current job at least 3 years. (Table -2 Hameed and Allo (2018) revealed that there were significant statistical differences in nurses' techniques of blood pressure measurement in regard to their educational level. Our study revealed that nurses whose years of experience group (6-10) years have more knowledge and nurses whose years of experience group (21 and more) have lowest knowledge .…”
Section: Discussionmentioning
confidence: 99%
“…Data have been analyzed through the use of simple statistical analysis and the inferential analysis that include: Analysis of variance and the researcher used the SPSS version 24.0 to analysis of data. Table (2) revealed that majority of answers were false (13) domains, while majority of true nurse's answers were (35(0.58%) in item (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation